Effects of environmental factors and forest management on landscape-scale forest storm damage in Turkey - Torun, Pakize; Altunel, Arif Oguz (Springer Science and Business Media LLC, 2020)
Context: Excessive wind cause serious damages to individual trees and forest stands. When unintentionally coupled with the forest management preferences, catastrophic levels of damage might be unavoidable.Aims: The main objective was to assess the environmental factors contributing to the impact of a strong windstorm that occurred between March 14 and 15, 2013 and resulted in 1.5-million m3 timber losses in the Kastamonu Regional Directorate of Forestry.Methods: Maximum entropy modeling (Maxent) and geographic information systems (GIS) were used to evaluate the factors contributing to the forest damage.Results: Stand type, diameter class, and elevation were the most important variables affecting the level of wind damage. The pure and mixed coniferous stands were the hardest hit when compared with the deciduous stands. The damage increased as the density of forest roads grew.Conclusion:It was concluded that windstorms pose serious threats to Turkish forests. Storm damage risks must therefore be integrated into forest management. In order to better understand the environmental factors contributing to the destructive effects of windstorms in forests, it would be best to focus on the telltale signs pointing the wrong-doing in forest management preferences at larger environmental scale rather than looking for reasons behind the occurrences of scattered small-scale damage.
Keywords: Forest management; GIS; Environmental influences; [SDE.IE] Environmental Sciences/Environmental Engineering; Maxent; [SDV.SA.SF] Life Sciences [q-bio]/Agricultural sciences/Silviculture, forestry; Storm damage; Stand stability; 15. Life on land; 13. Climate action; 11. Sustainability